Improving the Lifeskills of the PROLANIS Group Through the Android-Based Application SIPEGI: Chronic Kidney Disease Information System in Kidney Disease Prevention - lailatul kodriyah; Wiwit Dwi Nurbadriyah; Ardhiles Wahyu Kurniawan (Institut Kesehatan YARSI Mataram, 2026)
Chronic Kidney Disease (CKD) increases every year, so life skills are needed in preventing kidney disease. Prevention needs to be done in risk groups who already have chronic diseases. PROLANIS is a Chronic Disease Management Program, a group of people with hypertension and diabetes mellitus. These diseases are the biggest risk factors for CKD. An educational approach requires appropriate methods and means to improve Life Skills by maximizing Android facilities through the SIPEGI application (Chronic). This study aims to improve the life skills of the PROLANIS group through the SIPEGI Android-based application: Chronic Kidney Disease Information System in preventing kidney disease. The study used a pre-experimental design. The sample was the PROLANIS group with the following criteria: PROLANIS members from Kepanjen District, Malang, cooperative, able to read and write, and own an Android. The sample size was 30 people with a purposive sampling technique. The variables studied were life skills in preventing kidney disease. The instrument used a pre- and post-test questionnaire with intervention in the form of SIPEGI education. The Wilcoxon statistical test obtained a p value of 0.001, meaning that there was an increase in the life skills of the PROLANIS (Chronic Disease Management Program) group through the SIPEGI Android-based application.